MANAJEMEN DAKWAH MASJID AL-IMAN KABUPATEN PADANG LAWAS: M ARIF EFENDI - Efendi, M Arif (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
This research is field research with a qualitative approach. Research materials were obtained from primary and secondary data. The main data source was obtained from the Ta'mir Al-Iman mosque and congregation, while secondary data came from observation, interviews and documentation. After collecting data, researchers used the Milas and Huberman data analysis model, namely data reduction, data, data display (data presentation) and inference (making conclusions). The results of this research show that in general it can be said that this mosque has not functioned optimally as a regional mosque, but in terms of mission management, the management function of the Al-Iman Mosque has been implemented as seen in the picture. layout. Prospect has a clear work program and organizationally counts managers according to their departments, in relation to the chairman Ta'mir has fulfilled his main duties, including motivating, leading and communicating with other managers. Based on the inspection, they carried out an evaluation in the form of a report that could be accounted for at the end of the implementation of the Al-Iman Mosque.